Adverse Events in Orthopaedics. Issue 7 (July 2015) - Sathiyakumar, Vasanth; Thakore, Rachel V.; Greenberg, Sarah E.; Whiting, Paul S.; Molina, Cesar S.; Obremskey, William T.; Sethi, Manish K.
<x xml:space="preserve">Abstract</x> Objectives: As our healthcare system moves toward bundling payments, orthopaedic trauma surgeons will be increasingly benchmarked on perioperative complications. We therefore sought to determine financial risks under bundled payments by identifying adverse event rates for (1) orthopaedic trauma patients compared with general orthopaedic patients and (2) based on anatomic region and (3) to identify patient factors associated with complications. Design: Prospective. Setting: Multicenter. Patients/Participants: A total of 146, 773 orthopaedic patients (22, 361 trauma) from 2005 to 2011 NSQIP data were identified. Interventions: Minor and major adverse events, demographics, surgical variables, and patient comorbidities were collected. Main Outcome Measurements: Multivariate regressions determined significant risk factors for the development of complications. Results: The complication rate in the trauma group was 11.4% (2554/22, 361) versus 4.1% (5137/124, 412) in the general orthopaedic group (P = 0.001). When controlling for all variables, trauma was a risk factor for developing complications [odds ratio (OR): 1.69, 95% confidence interval (CI): 1.57–1.81]. After controlling for several patient factors, hip and pelvis patients were 4 times more likely to develop any perioperative complication than upper extremity patients (OR: 3.79, 95% CI: 3.01–4.79, P = 0.01). Lower extremity patients are 3 times more likely to develop any complication versus upper extremity patients (OR: 2.82, 95% CI: 2.30–3.46, P = 0.01). Conclusions: Our study is the first to show that orthopaedic trauma patients are 2 times more likely than general orthopaedic patients to sustain complications, despite controlling for identical risk factors. There is also an alarming difference in complication rates among anatomic regions. Orthopaedic trauma surgeons will face increased financial risk with bundled payments. Level of Evidence: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.